2001
DOI: 10.1046/j.1365-2591.2001.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of yeasts and enteric bacteria in root‐filled teeth with chronic apical periodontitis

Abstract: The high prevalence of enteric bacteria and yeasts in root-filled teeth with chronic apical periodontitis was established. IKI improved the antimicrobial effect of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
297
1
30

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(355 citation statements)
references
References 21 publications
9
297
1
30
Order By: Relevance
“…Anaerobic bacteria, especially Gram-negative species of Prevotella and Porphyromonas, are frequently associated with signs and symptoms of endodontic origin [2][3][4], and facultative species such as Enterococcus faecalis have been isolated in high frequency from refractory cases [5]. E. faecalis is rarely observed in cases of primary infections, but has been found to be the major component of microfl ora in cases of retreatment, amounting to as much as 70% of the microbiota isolated in these cases [6].…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic bacteria, especially Gram-negative species of Prevotella and Porphyromonas, are frequently associated with signs and symptoms of endodontic origin [2][3][4], and facultative species such as Enterococcus faecalis have been isolated in high frequency from refractory cases [5]. E. faecalis is rarely observed in cases of primary infections, but has been found to be the major component of microfl ora in cases of retreatment, amounting to as much as 70% of the microbiota isolated in these cases [6].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of pulp necrosis with radiographic sign of apical periodontitis and lack of periodontal disease, E. faecalis was isolated in 55% (4) and 64% of the cases (2). Microbiological identification and analytic studies of teeth presenting endodontic treatment and periapical lesion verified that this microorganism is the most prevalent species, present in 45% (3), 77% (5) and up to 77.8% (6) of the cases.…”
Section: Introductionmentioning
confidence: 91%
“…However, Bystrom and Sundqvist (1) showed that microorganisms can survive even after biomechanical preparation and Enterococcus faecalis (Gram-positive, facultative anaerobic coccus) has been frequently isolated in root canals exhibiting persistent post-endodontic treatment infections (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…17,51,52 Enterococci, which are seldom found in these circumstances, have been isolated from teeth undergoing endodontic treatment and previously root treated teeth. [53][54][55][56] In a study of root filled teeth with apical periodontitis 69% of the bacterial strains recovered from the root canals were faculative anaerobes. 53,54 Enterococci were isolated in 50% of the infective cases and were the most frequently isolated.…”
Section: Endodonticsmentioning
confidence: 99%